2021
DOI: 10.1001/jamanetworkopen.2021.23923
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Enhanced Liver Fibrosis Test to Estimate Advanced Fibrosis Among Patients With Nonalcoholic Fatty Liver Disease

Abstract: This cross-sectional study investigates use of the noninvasive enhanced liver fibrosis test to estimate advanced fibrosis among patients with nonalcoholic fatty liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…In the study by Harrison et al, the ELF test demonstrated satisfying accuracy for detecting significant (cutoff −0.2) and advanced fibrosis (cutoff −0.1) among NASH patients [ 20 ]. Younossi et al reported very high specificity of the ELF test and good reliability in ruling in patients with advanced fibrosis (cutoffs 9.8 and 11.3) among NAFLD patients with biopsy and VCTE as reference tools [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Harrison et al, the ELF test demonstrated satisfying accuracy for detecting significant (cutoff −0.2) and advanced fibrosis (cutoff −0.1) among NASH patients [ 20 ]. Younossi et al reported very high specificity of the ELF test and good reliability in ruling in patients with advanced fibrosis (cutoffs 9.8 and 11.3) among NAFLD patients with biopsy and VCTE as reference tools [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This SLR provides a comprehensive current overview of diagnostic tools for detection and monitoring of NASH-related liver fibrosis staging based on the summarized evidence from the US studies. The diagnostic accuracy was validated against liver biopsy as a standard diagnostic tool in all studies, except for the Caussy et al study where both liver biopsy and MRE were used [ 29 ], and that of Younossi et al where VCTE and biopsy were reference tools [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that investigated the diagnostic accuracy of ELF in 829 patients with NAFLD demonstrated that the AUROC for advanced fibrosis was 0.81. Furthermore, the performance of ELF was similar regardless of age or diabetes mellitus 32 . Another study demonstrated that the diagnostic accuracy of ELF is comparable to an imaging‐based modality 33 …”
Section: Noninvasive Fibrosis Markers In Nafldmentioning
confidence: 90%
“…Furthermore, the performance of ELF was similar regardless of age or diabetes mellitus. 32 Another study demonstrated that the diagnostic accuracy of ELF is comparable to an imaging-based modality. 33 Type IV collagen 7S is a fragment of type IV collagen, which consists basement membrane.…”
Section: Direct Fibrosis Markersmentioning
confidence: 99%
“…[ 55 ] Combining the ELF score < 7.2 with the FIB‐4 score < 0.74 may provide even greater sensitivity (92.5%) for ruling out advanced fibrosis. [ 56 ] Given the probability of more rapid progression of NASH in patients with AGHD, all patients with suspected liver fibrosis ≥ stage 2 should be followed closely by a hepatologist. Figure 2 represents a suggested screening algorithm.…”
Section: Screening Patients With Aghd For Nafld?mentioning
confidence: 99%